Novel synthesis of 3-((benzo[d]thiazol-2-ylamino)(phenyl)methyl)-4-hydroxy-1-methylquinol in-2(1H)-one via consecutive C-C and C-N bond formation in water - Yadav, Maruti B.; Vagh, Sandip S.; Jeong, Yeon Tae (Research on Chemical Intermediates, 2020)
A simple, efficient, and eco-friendly protocol has been developed for the synthesis of novel 3-((benzo[d]thiazol-2-ylamino)(4-methoxyphenyl)methyl)-4-hydroxy-1-met hylquinolin-2(1H)-one derivatives using a one-pot C-C and C-N bond forming strategy from the reaction of 4-hydroxy-1-methylquinolin-2(1H)-one, 2-aminobenzothiazole and aromatic aldehydes in aqueous solvent without using any metal catalyst. Several advantages of this protocol include its operational simplicity, short reaction time, mild reaction condition, efficient utilization of all the reactants, wide functional group tolerance, using water as an environmentally friendly solvent and non-chromatographic purification procedure. [GRAPHICS] .
Keywords: 4-Hydroxy-1-methylquinolin-2(1H)-one; Green solvent; Multicomponent reactions (MCRs); Quinolines; Thiazole